KETERKAITAN ANTARA KEPERCAYAAN DAN KEPUASAN PENGGUNA SMART CARD (STUDI PADA PENGGUNA KARTU Flazz BCA) - , Meuthia, SE., Dr. Hargo Utomo, MBA., M.Com. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to examine the relationship between trust and satisfaction of smart cardâs users. The main impetus of this research is motivated by empirical studies on trust which are still divergent. Diversity of studies through the domains that describe the dimensions and the debate about concept of trust have indicated the need for more specific analysis of the relationship between trust and satisfaction as the outcome of trustâs constructs. This research uses quantitative approach through an online survey of 117 respondents who have become Flazz BCA cardâs users in Indonesia. The tool of analysis is Structural Equation Modelling (SEM) with Partial Least Square (PLS) software. The research found that trust was not a major concern in the context of smart card. Cognitive stimuli and emotional that affect the system of human brain activity to have confidence when making decision or giving an assestment of things are not fully encouraging satisfaction on the users. There are other factors that become stimulants for the fulfillment of Flazz BCA card usersâ satisfaction, which focus on information quality, system quality, and participation of users. High perceived risk when followed by high level of trust was also a stimulant for being high level of participation which ultimately increases usersâ satisfaction, eventhough the users give less rating for the quality of services on Flazz BCA card product.